The Voyage of the Vénus - Belhacel, Abdelhakim (2022)
ABDELHAKIM BELHACEL (Paris) presented the voyage of the Vénus, a French vessel under the command of François Étienne de Rosily-Mesros, and the vessel Prévoyante, in 1785, which traveled to Comoros, Mauritius, and eastern Africa. The primary aim of this expedition was to establish a French colony in Mongalo near Zanzibar, which could serve as the base for the ivory and slave trade. In this region, different geopolitical interests were at play at the time: The local Mongalo saw the French as their ally against the Portuguese of Mozambique. A short-lived French colony existed from 1786 to 1790 before it went bankrupt and was quickly dismantled by orders of the Sultan. The expedition of these two vessels was generally regarded as a success.
Keywords: Relations – Zanzibar – France